Clinical value of serum bone resorption markers for predicting clinical outcomes after use of bone modifying agents in metastatic bone tumors: A prospective cohort study. Issue 12 (28th December 2019) - Urakawa, Hiroshi; Ando, Yuichi; Hase, Tetsunari; Kikumori, Toyone; Arai, Eisuke; Maeda, Osamu; Mitsuma, Ayako; Sugishita, Mihoko; Shimokata, Tomoya; Ikuta, Kunihiro; Ishiguro, Naoki; Nishida, Yoshihiro
Abstract : Bone modifying agents (BMAs) have become a standard treatment to prevent skeletal‐related events (SREs) in bone metastases (BMs). The aim of our study is to determine the clinical value of serum bone resorption markers for predicting clinical outcomes after using BMAs in patients with BM. Patients were enrolled between May 2013 and October 2017 at the Nagoya University Hospital, Japan. We prospectively observed changes in pyridinoline cross‐linked carboxyterminal telopeptide of type I collagen (ICTP) and tartrate‐resistant acid phosphatase 5b (TRACP‐5b) during treatment with BMAs. The relationship between serum markers before and after treatment and clinical outcomes such as progression of bone disease (BD), SREs and overall survival (OS) were evaluated. Pearson chi‐square test and Kaplan–Meier product limit methods were used for analysis. Sixty‐seven patients were analyzed. The primary tumor sites were 21 lung, 16 breast and 30 others. Forty and 27 patients were treated with Denosumab and Zoledronic acid, respectively. Progression of BDs, SREs and death were observed in 10, 16 and 31 cases, respectively. The median follow‐up period after using BMAs was 12.3 (range 0.3–66.3) months. ICTP at 3–4 weeks was significantly correlated with increasing BD progression, SREs and death after treatment in both the whole and lung cancer cohorts. Base line ICTP and TRACP‐5b were also associated with increasing BD progression in the whole cohort. Our study showed that early posttreatment ICTP is useful for predicting BD progression, SREs and OS after use of BMAs in patients with BM and even in patients with lung cancer BM. Abstract : What's new? Bone modifying agents (BMAs) have become a standard treatment to prevent skeletal‐related events (SREs) in bone metastases. This study assessed the clinical value of serum bone metabolism biomarkers ICTP and TRACP‐5b to predict disease progression, SREs, and overall survival after BMA treatment in 67 lung, breast, and other cancer patients with metastatic bone disease (BD). High ICTP at 3–4 weeks after the start of BMA use was significantly associated with progression of BD, increasing SREs, and death in both the whole and lung cancer cohorts. Baseline ICTP and TRACP‐5b were also associated with increasing BD progression in the whole cohort.